Crop response to biochar under differing irrigation levels in the southeastern USA. Issue 3 (4th May 2018) - Lamb, Marshall C.; Sorensen, Ronald B.; Butts, Christopher L.
ABSTRACT: Application of biochar to soils is hypothesized to increase crop yield. Crop productivity impacts of biochar application in southeastern cropping systems consisting of peanut ( Arachis hypogaea L.), corn ( Zea mays L.), and cotton ( Gossypium hirsutum L.) produced under varying rates of irrigation have not been addressed. This research incorporated biochar at two different rates into a long-term irrigation and cropping systems study to compare yield and quality response of peanut, corn, and cotton. Biochar was incorporated into soil once at the beginning of the 4-year project at rates of 22.4 and 44.8 Mg ha −1 . Peanut, corn, and cotton were produced under three sprinkler irrigation levels (100%, 66%, and 33%), shallow surface drip irrigation (100%), and a nonirrigated control. Crop input management followed best management practices. Sprinkler irrigation was scheduled by Irrigator Pro for Peanuts, Corn, and Cotton at the 100% level and the 66% and 33% levels were applied at the same time as the 100% level. Significant year, irrigation, and year × irrigation effects for corn, cotton, and peanut yield resulted ( p  < 0.001). No differences resulted for biochar in corn ( p  = 0.930) or cotton ( p  = 0.678). Peanut yield showed a significant response to biochar comparing the 44.8 Mg ha −1 rate to the untreated control in nonirrigated production at the p  = 0.05 level and in the 33% irrigated treatment at the p  = 0.10 level. No negative effects resulted from biochar opening opportunities for biochar application in southeastern U.S. cropping systems for purposes related to carbon sequestration without compromising productivity of producers and related agricultural sectors.